Konsumen Hijau (Green Consumer): Tren Perilaku Pembelian Berbasis Kesadaran Lingkungan - Ni Wayan Dita Melani; Nyoman Dwika Ayu Amrita; Ni Komang Dewi Syahrani; Ni Luh Rita Dewi; I Putu Surya Andika (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2025)
Growing public concern for environmental issues has driven the emergence of green consumers as an increasingly influential market segment. This study aims to analyze trends in environmentally conscious purchasing behavior and identify the key factors that influence consumers’ intentions and decisions when choosing eco-friendly products. Through a literature-based approach, the findings indicate that environmental awareness, positive attitudes toward sustainability, perceived ecological benefits, and green brand image are primary drivers of green purchasing behavior. Authentic and consistent green marketing strategies strengthen purchase intention by communicating sustainability values, presenting eco-labels, and emphasizing corporate social responsibility. In addition, psychological factors such as personal concern, social norms, and perceived behavioral control contribute to consumers’ tendency to select sustainable products. Overall, the trend of green consumers continues to rise, offering significant opportunities for businesses to develop ethical, informative, and environmentally oriented marketing strategies that align with the expectations of modern markets. Keywords: Green Consumer, Purchasing Behavior, Green Marketing, Environmental Awareness, Green Purchase Intention.